PENGARUH MINAT BELAJAR SISWA TERHADAP PRESTASI BELAJAR MATEMATIKA DI SMKN 1 CIHAMPELAS - Irna Daulatina Islamiah (Journal on Education, 2019)
This study aims to describe the influence of student learning interest and mathematics learning achievement of students of SMK 1 Cihampelas. Types of quantitative research. The population in this study was the tenth grade students of the Computer Networking Engineering Program at SMK 1 Cihampelas in the odd semester of the 2018-2019 academic year. The research method used in this study using correlational analysis. Samples were obtained by using simple random sampling techniques as many as 36 students from class X of SMK 1 Cihampelas. Data collection is done by giving questionnaires and PTS tests. Data analysis was performed using SPSS 23 program assistance consisting of descriptive analysis analysis, test requirements for data analysis and hypothesis testing. Requirements test for data analysis used, namely normality test, and linearity test. Obtained from the conclusion of the study that there is a significant positive influence between interest in learning towards mathematical learning achievement